PERAN MAJALAH AL-FIKRAH DALAM MENGEMBANGKAN DAKWAH BIL QOLAM KHAS PESANTREN - Tiara Dian Ayu Fernanda; Noviana Aini (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
Media is a means of communication for the community, which is located between two parties, namely as intermediaries and liaisons. Media is a tool or means used to convey messages from communicators to audiences. In this day and age, da'wah media is a factor that determines the success of da'wah. Da'wah media has an important role for da'wah that is carried out because da'wah media is a component that is intertwined with one another to achieve da'wah goals. One of mass communication media is print media. namely mass media that use paper as a forum to convey written messages to their audiences or readers. The process of delivering messages through mass media is termed journalism activities. What makes the print media demands the expertise of the da'i in the world of writing. Da'i must be able to package his writings clearly and be skilled in the preparation of good words that can be understood by the reader. For the da'i understanding of the world of journalism is needed. Al-Fikrah magazine as a medium of information and Islamic thought and can be used as a medium for Islamic boarding school propaganda that is accepted by the wider community. This magazine tries to answer the challenges of the times and the globalization of the media and the needs of Muslims. Therefore, the formulation of the problem in this research are: (1) How is the Role of Al-Fikrah Magazine in Developing Bil Qolam Da'wah Typical of Islamic Boarding Schools (2) How is Bil Qolam's Da'wah in Al-Fikrah Magazine Typical of Islamic Boarding Schools.This study uses a qualitative approach, because it aims to determine the role of Al-Fikrah Magazine in developing da'wah bil qolam typical of pesantren and know the da'wah of bil qolam in Al-Fikrah Magazine typical of pesantren with theory role. The results showed that the role of magazinesal-fikrah The role of Al-Fikrah Magazine in developing the typical Islamic boarding school bil qolam da'wah is as a forum for students' writing creativity. Bil Qolam's Da'wah in the Al-Fikrah Magazine Typical of the Pesantren is namely the Al-Fikrah Magazine, can realize the thoughts of students and the existence of this media as an inspiration for students to devolep creativity in journalism.Keywords: Role of Al-Fikrah Magazine, Bil Qolam Da'wah, Islamic Boarding School.